History, biography, and the genre of Luke-Acts an exploration of literary divergence in Greek narrative discourse - Pitts, Andrew W. (Boston BRILL, 2019)
Intro -- Contents -- Tables and Figures -- Abbreviations -- Chapter 1 Genre and Method in Luke-Acts Research -- 1 The Origins of a Consensus -- 2 What Went Wrong? -- 3 What is the Solution? 'New' Genre Studies as a Way Forward -- 4 Genre Agnation and the 'New' Genre Studies -- 5 Typological Agnation Analysis: Assessing Genre Differences -- 6 Topological Agnation Analysis: Proximating Genre Likeness -- 7 Conceptions of History and Biography in Antiquity -- 8 Evolutionary Topology and Genre Proximity -- 9 Genre Elasticity and Blurring -- 10 Typological Analysis of Greek Historical Genres -- 10.1 Feature Clusters in Genre Agnation -- 10.2 Feature Clusters in Burridge's Model of Genre -- 10.3 Feature Clusters in Adams' Model of Genre -- 10.4 The Contribution of Feature Cluster Analysis to Genre Study -- 11 Feature Clines and Genre Analysis: a Methodological Outline -- 12 Linguistic Hierarchy, Macrostructural Analysis, and Macrogenre -- 13 Conclusions -- Chapter 2 Identifying Greek History and Biography -- 1 What is a 'Representative' Corpus and Why is it Important? -- 2 Toward a Representative Corpus of the Greek History Genre -- 3 Toward a Representative Corpus of the βίος Genre -- 3.1 Biographical Predecessors -- 3.2 The Collected Greek βίοι -- 3.3 The Individual Greek βίος -- 4 Corpus Linguistics, Gospel Studies, and Richard Burridge -- 5 Conclusions and Implications -- Chapter 3 Topical Focus and Participant Identification -- 1 Topical Focus: Activity vs. Entity -- 1.1 Activity Focus in the Greek History -- 1.2 Entity Focus in the βίος -- 1.3 Focus in the Gospels with Special Reference to Luke -- 1.4 Focus in Acts -- 2 Participant Identification: Generic vs. Individualized -- 2.1 Generic Participant Identification in Histories -- 2.2 Individualized Participant Identification in the βίος.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Bible.-Acts-Criticism, interpretation, etc; Bible.-Luke-Criticism, interpretation, etc